A parallel yet divided information space: testing the overlap of Yandex Russian language news media discourses in Estonia, Latvia, and Russia. Issue 3 (2nd September 2019) - Erbsen, Heidi
ABSTRACT: In recent years, academics, politicians, and international news media have speculated about the influence Russia is capable of wielding, particularly among Russian speaking populations in the near abroad. This paper aims to reassess the unity or division of a common Russian language information space through an analysis of the top daily headlines presented in Yandex. Based on previous historical overviews of Russian political discourses on Europe and analysis of more recent discourses in Russian television, frames for analysis are proposed and compared with actual headlines collected in real from Yandex news concerning Estonia, Latvia, and Russia.